Superparamagnetic iron-oxide based nanoparticles for the separation and recovery of precious metals from solution - Lakay, Eugene Marlin (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.